Extraction of antioxidants amount in cocoa leaves / Naemah Tajol Arus - Arus, Naemah Tajol (Faculty of Applied Sciences, 2009)
Cocoa leaves were processed according to green tea extraction processing procedures. Polyphenol components EGC and ECG were extracted and analyzed using high pressure liquid chromatography (HPLC). The best results were obtained with distilled watermethanol- acetic acid at a flow rate of 0.8 ml /min which allowed the separation of catechins within 10 min. Concentration of antioxidant in cocoa leaves was higher EGC which is 31.4 ppm followed by tea leaves, 30.1 ppm using methanol. Cocoa also higher concentration in ECG where the reading 19.8 ppm and tea 16.5 ppm with the same extraction .By using water the reading bit different in EGC where the cocoa leaves gives reading lower than tea leaves .Cocoa leaves only contain 24.7 ppm compare 30 ppm in tea leaves.ECG was not appear in water extraction